Association of New Mutant Allele, w4‐nw, at W4 Locus with Near‐White Flower Color in Soybean. Issue 4 (1st July 2016) - Park, Gyu Tae; Sundaramoorthy, Jagadeesh; Lee, Jeong‐Dong; Kim, Jeong Hoe; Park, Soon‐Ki; Seo, Hak Soo; Song, Jong Tae
Abstract : An ethyl methanesulfonate‐induced mutant (PE1033) with near‐white flowers was isolated from the soybean [ Glycine max (L.) Merr.] cultivar Pungsannamul with purple flowers that had the W1w3W4 genotype. In the present study, we aimed to investigate the genetic and molecular bases of the flower color variation displayed by the PE1033 mutant. Analyses of genomic sequences and reverse transcription–polymerase chain reaction (RT‐PCR) revealed that the color variation of PE1033 flowers originated from a recessive mutation in the W4 locus that encodes dihydroflavonol 4‐reductase (DFR) 2. The new mutant allele, named w4‐nw, harbored a single‐nucleotide substitution (G to A) at the 5′ spliceosome recognition site in the first intron of DFR2, resulting in the failure of splicing and producing two different abnormal transcripts: w4‐nw‐a and w4‐nw‐b . The former encoded a truncated DFR2 protein because of the occurrence of a premature stop codon in the first intron, which was retained in the transcript; the latter resulted from alternative splicing of the first intron and encoded a DFR2 protein that lacked 11 amino acid residues in the N‐terminus. Derived cleaved amplified polymorphism sequence (dCAPS) analysis revealed a tight cosegregation pattern between the w4 ‐ nw mutant allele and near‐white color phenotype. In conclusion, the novel mutation in the W4 locus, w4‐nw, caused the production of near‐white flowers under the w3 allelic background of PE1033.